Using Human Embryonic Stem Cells (hESCs) as an In Vitro Model for Environmental Contaminant Embryotoxicity Testing - Li, Bai (Université d'Ottawa / University of Ottawa, 2023)
Early embryo development is one of the most sensitive stages to environmental chemicals during the whole life. Prenatal exposures to many environmental chemicals have been shown to impact fetal development and be associated with adverse health outcomes in later life stages. However, the effects of chemical mixture exposure on developing embryos, especially in early developmental stages, have yet to be fully studied. To fulfill this research gap, my thesis was divided into three data chapters and mainly aimed at investigating the effects of a chemical mixture on human early-stage embryo development. In Chapter 2, I chose methylmercury (MeHg) as the main study toxicant to establish procedures for embryotoxicity testing using human embryonic stem cells (hESCs). I then characterized the effects of low doses of MeHg on this stem cell model by screening a set of cell fate decision-related makers and found MeHg is embryotoxic, which is consistent with epidemiological and in vivo findings. In Chapter 3, I studied the embryotoxicity of a chemical mixture that consists of 23 individual environmental chemicals (including MeHg) detected from the maternal blood samples of pregnant women in Nunavik, labelled as Nunavik Contaminant Mixture (NCM), using the same cell model. The effects of NCM exposure on hESCs were compared to MeHg exposure alone. NCM exposure adversely affected cell viability and adhesion, induced apoptosis, disrupted the cell cycle, altered the expression of cytoskeleton and autophagy proteins, and changed the levels of lineage marker gene and protein expressions in a dose-dependent manner. Some distinct effects on hESCs between NCM exposure and MeHg alone exposure were noticed, and the potential interactions among the chemical components within a chemical mixture were indicated. In Chapter 4, I studied the effects of MeHg exposure during the formation of definitive endoderm (DE) cells from hESCs and compared that to MeHg's effects on undifferentiated hESCs. I found that cell specification towards endoderm could be affected by MeHg exposure, mainly through disrupting calcium homeostasis and over-generating reactive oxygen species, leading to increased ribosome biogenesis and protein synthesis. Moreover, MeHg effects are state-dependent; MeHg enhances pluripotency in undifferentiated hESCs, but it promotes differentiation during DE induction. Taken together, this thesis verifies the value of hESCs in testing the embryotoxicity and developmental toxicity of environmental chemicals, enriches the understanding of the toxicity of MeHg and NCM, emphasizes the necessity of evaluating the effects of chemical mixtures and provides new directions in studying environmental chemical toxicity using stem cells. Findings from my thesis could hopefully contribute to predicting the potential effects of prenatal environmental chemical exposures and aid in developing evidence-based public health policy.
Keywords: Human embryonic stem cell; Chemical mixture; Methylmercury; Risk assessment